The impact of informal caregiving on the mental health of health care workers during the COVID-19 pandemic—cross-sectional and longitudinal results from the VOICE study - Wintermann, Gloria-Beatrice; Bornhorn, Anne Irmgard; Steudte-Schmiedgen, Susann; Albus, Christian; Baranowski, Andreas M.; Beschoner, Petra; Erim, Yesim; Geiser, Franziska; Jerg-Bretzke, Lucia; Morawa, Eva; Mogwitz, Sabine; Weidner, Kerstin (Frontiers in Public Health, 2025)
BackgroundThe COVID-19 pandemic increased psychological distress among health care workers (HCWs). Those with informal caregiving responsibilities (ICs) may be especially vulnerable, but data remain limited.MethodsIn a multicenter online survey conducted across four time points (T1–T4: 2020–2022) within the German healthcare system, HCWs with ICs were compared to those without (comparison group, CG). Psychological distress was assessed using validated measures of anxiety (Generalized Anxiety Disorder/GAD-2) and depression (Patient Health Questionnaire/PHQ-2). Group differences were analyzed using non-parametric Mann–Whitney U and chi-square tests. Longitudinal logistic regression analyses examined the impact of IC on psychological distress, controlling for sociodemographic, occupational, and psychological factors. A moderation analysis tested whether fear of infecting relatives influenced the salutogenic effect of optimism. All analyses were performed with multiply imputed data and a retrospective sample size justification was conducted.ResultsICs were more likely to be female, older, work in occupations other than medicine, work part-time, have children, and have more than 6 years of work experience. While ICs showed significantly higher PHQ-4 anxiety and depression than CG at T1 and T2, no significant differences could be shown for the other time points. IC emerged as a significant risk factor for increased psychological distress longitudinally, even after controlling for confounders. The protective effect of optimism was moderated by fear of infecting relatives at T1.ConclusionHCWs with informal caregiving duties represent a vulnerable subgroup with increased psychological distress, especially during the early pandemic. This group may benefit from targeted support (e.g., flexible schedules, protective equipment, psychological interventions). Limitations include lack of pre-pandemic data and reliance on self-report. Findings underscore the importance of acknowledging and addressing overlapping care burdens in future health crises.